2013
DOI: 10.1017/s0022109012000646
|View full text |Cite
|
Sign up to set email alerts
|

Executive Compensation and Business Policy Choices at U.S. Commercial Banks

Abstract: We show that contractual risk-taking incentives for chief executive officers (CEOs) increased at large U.S. commercial banks around 2000, when industry deregulation expanded these banks’ growth opportunities. Our econometric models indicate that CEOs responded positively to these incentives, especially at the larger banks best able to take advantage of these opportunities. Our results also suggest that bank boards responded to higher-than-average levels of risk by moderating CEO risk-taking incentives; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(73 citation statements)
references
References 50 publications
(83 reference statements)
4
61
0
Order By: Relevance
“…Next, bank stocks are sorted into the first and third quantiles to create a high-inside-debt portfolio and a low-inside-debt portfolio. This paper's focus on debt-based compensation adds to recent work that studies the role of nondebt incentives and risk taking in the financial sector's problems (e.g., Cheng et al (2012), Balachandran, Kogut, andHarnal (2010), DeYoung, Peng, andYan (2013), and Fahlenbrach and Stulz (2011)), in particular, risk-shifting problems (e.g., Chesney, Stromberg, and Wagner (2012)). Figure 1 illustrates the central claim of this paper that large inside debt holdings encourage managers to act conservatively, resulting in lower risk and smaller losses during the crisis.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…Next, bank stocks are sorted into the first and third quantiles to create a high-inside-debt portfolio and a low-inside-debt portfolio. This paper's focus on debt-based compensation adds to recent work that studies the role of nondebt incentives and risk taking in the financial sector's problems (e.g., Cheng et al (2012), Balachandran, Kogut, andHarnal (2010), DeYoung, Peng, andYan (2013), and Fahlenbrach and Stulz (2011)), in particular, risk-shifting problems (e.g., Chesney, Stromberg, and Wagner (2012)). Figure 1 illustrates the central claim of this paper that large inside debt holdings encourage managers to act conservatively, resulting in lower risk and smaller losses during the crisis.…”
Section: Figurementioning
confidence: 95%
“…In addition, DeYoung et al (2013) find that equity-based risk incentives have encouraged CEOs at U.S. commercial banks to generate more income from noninterest banking activities. To examine this, I follow DeYoung et al (2013) and measure the fraction of total noninterest income as total noninterest income scaled by net operating income (noninterest income + interest income -interest expense). To examine this, I follow DeYoung et al (2013) and measure the fraction of total noninterest income as total noninterest income scaled by net operating income (noninterest income + interest income -interest expense).…”
Section: Business Policy: Noninterest-based Bankingmentioning
confidence: 99%
“…DeYoung et al . () show that before the onset of the financial crisis (2000–2006), U.S. banks’ CEO compensation was changed to encourage executives to exploit new growth opportunities created by deregulation and debt securitization. Subsequently CEOs took more risk.…”
Section: Remuneration Of Executivesmentioning
confidence: 99%
“…A bank CEO with incentive pay might take more risks through a risky policy while improving performance. DeYoung et al (2010) found that CEO incentives do have an impact on bank risk taking. Felix Suntheim (2010) found that CEOs with strong incentives do motivate bank managers to engage in higher risk-taking policies in terms of a higher ratio of non-interest income (e.g.…”
Section: Incentive Pay and Bank Performancementioning
confidence: 99%